PENGARUH KOMITE AUDIT DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA SEBELUM DAN SESUDAH KONVERGENSI IFRS - Vivi Anggriani; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the effect of audit committee and managerial ownership as an independent variabel on earning management before and after convergence and also examine the difference effect of audit committee and managerial ownership on earning management before and after convergence of IFRS in Indonesia. The audit committee consist of the audit committee size, audit committee independence, audit committee expertise, and audit committee meeting.The type of data used in this study is secondary data and involves 40 non financial sector companies in Indonesia. the sampling metodh in this research uses purposive sampling technique for the company that has been listed in Indonesia Stock Exchanges which publishes annual report in 2008 until 2015. The data was analyzed separately between two period by using multiple linear regression model. This research also used Chow test as an additional test.This study uses agency theory to formulate five hypotheses that lead to the results of the analysis. The result of this showed that on before convergence of IFRS period, audit committee size, audit committee independence, and audit committee expertise has significant and negative effect on eraning management. However, on after convergence of IFRS period only audit committee independence and audit committee expertise have significant and negative effect on earning management. The result of chow test showed that the effect of audit committee and managerial ownership on earning management have structural change in regression model.